2011
DOI: 10.1159/000324523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Risperidone on Learning and Memory in Naive and MK-801-Treated Rats

Abstract: Background/Aims: The aim of this study was to investigate the effects of an atypical antipsychotic risperidone (RIS; 0.06, 0.125 or 0.25 mg/kg, intraperitoneal, i.p.) on learning and memory processes, both in naive and MK-801-treated (0.15 mg/kg, i.p.) rats. Methods: Modified elevated plus maze (mEPM), passive avoidance (PA) and Morris water maze (MWM) tasks were used. Results: In the mEPM test, RIS (0.125 or 0.25 mg/kg) significantly decreased the transfer latency and reversed MK-801-induced prolongation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 63 publications
4
7
0
Order By: Relevance
“…The experimental room was under controlled temperature (22 ± 2°C) and the behavioral testing was conducted using the mEPM learning test [9,15], the classical elevated plusmaze paradigm [32,33] and the open field test, as previously described [34,35]. All injections were done at a volume of 1 ml/kg and all experiments were performed between 8:00 a.m. and 1:00 pm.…”
Section: Behavioral Measuresmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental room was under controlled temperature (22 ± 2°C) and the behavioral testing was conducted using the mEPM learning test [9,15], the classical elevated plusmaze paradigm [32,33] and the open field test, as previously described [34,35]. All injections were done at a volume of 1 ml/kg and all experiments were performed between 8:00 a.m. and 1:00 pm.…”
Section: Behavioral Measuresmentioning
confidence: 99%
“…Learning/memory function assessment was done using the mEPM learning test, which measures spatial long-term memory [9,15]. Transfer latency (TL, the time at which animals move from the open arm to the closed arm) was used as an index of learning and memory processes.…”
Section: Mepm Learning Testmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that gabapentin, a GABA analogue, enhances cognitive performance in naive mice (Celikyurt et al, 2011a). Also, we have been shown that risperidone augmented learning performance in naive (untreated) and MK-801-treated rats in the mEPM test and reduced the distance to the platform in MK-801-treated rats in the MWM test (Celikyurt et al, 2011b).…”
Section: Discussionmentioning
confidence: 80%